Alterações laríngeas em vendedores de feira livre - Gasques, Cris Vanessa (2013)
The professional voice has been studied in literature in various aspects and levels. However, no reference related to the professional voice of the barker has been found. Objective: describing the laryngeal alterations in sellers at public fairs in Aracaju-SE. Casuistic and methods: a descriptive study of transversal cut was done with quantitative approach. An interview was done along with a nasolaryngoscopy in 49 barkers. A descriptive analysis of data was applied. Results: there was a predominance of the feminine gender. The predominant age average was between 30 and 39 years old. The predominant symptomatology status was related to laryngeal-pharyngeal reflux disease. Laryngeal alterations were identified in all anatomic regions: subglottis, glottis and supraglottis. Conclusion: the laryngeal alterations were predominant in the subglottic region. These detected changes shows the need for further studies along with phonotrauma and other laryngeal diseases.